1996
DOI: 10.1021/jp960391x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Cumulenes C2NX2 (X = O or S):  Tandem Mass Spectrometry and ab Initio Studies

Abstract: New cumulenic ions, SNCCO + , SCNCO + , SNCCS + , and SCNCS + , have been generated by dissociative ionization and characterized by tandem mass spectrometry techniques. The stabilities of the corresponding radicals were evaluated by neutralization-reionization (NR) experiments and supported by ab initio molecular orbital calculations at the G2(MP2,SVP) level. The neutral radicals, SNCCS • , SCNCS • , and SNCCO • , are found by experiment and theory to be observable species in the gas phase, while SCNCO • is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The cumulenic ion OCN + CS has recently been formed and characterized in the gas phase 12a. With 2‐methyl‐1,3‐dioxolane, this interesting acylium‐thioacylium ion reacts uniquely (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulenic ion OCN + CS has recently been formed and characterized in the gas phase 12a. With 2‐methyl‐1,3‐dioxolane, this interesting acylium‐thioacylium ion reacts uniquely (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The instrument, denoted Q 1 q 2 Q 3 q 4 Q 5 , is composed of a sequential arrangement of three mass‐analyzing (Q1, Q3, Q5) and two ‘r.f.‐only’ ion‐focusing reaction quadrupoles (q2, q4). By 70 eV electron ionization (EI), appropriate precursors form the reactant acylium ions: ethoxycarbonyl isocyanate forms OCN + CO,11 benzoylacetone8 forms OCCH + CO and ethoxycarbonyl thyoisocyanate12 forms OCN + CS. When performing MS 2 ion–molecule reactions, Q1 was used to mass select the ion of interest for further reactions in q2 with a selected neutral reagent.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the development of new experimental techniques such as the neutralization-reionization (NR) procedures [1][2][3][4] made possible the identification of elusive chemical compounds, characterized by short lifetimes, as well as non-conventional compounds. In this respect the contributions of R. Flammang have been remarkable 5,6 and his work on cumulenes [7][8][9][10][11][12][13][14][15] is a paradigmatic example of his achievements in this field.…”
Section: Introductionmentioning
confidence: 99%
“…(Wong et al reported that the MS/MS/MS experiments on (C 2 ,N,S) ions in case of SNCCS and SCNCS isomers were inconclusive. 28 Another report by McGibbon et al indicates that the (C 2 ,N,S) ions derived from various precursor molecules give rise to virtually identical CA spectra. 33 ) We also found that (C 2 ,N,S) ions generated from various precursors including methylenedithiocyanate gave rise to identical CA spectra.…”
mentioning
confidence: 98%
“…14 Of the three [C 2 ,N,S 2 ] heterocumulene isomers, two of them, [S=C=C-N=S] /0 and [S=C-N=C=S] /0 , have been very well characterized by collisional activation and neutralization-reionization mass spectrometric (NRMS) [15][16][17][18][19][20][21][22][23][24][25][26] experiments. 27,28 Here we report the generation and characterization of the third isomeric species, thiocarbonylthiocyanate [S=C=S-C ---N] /0 , by the NRMS technique.…”
mentioning
confidence: 99%